2014
DOI: 10.7314/apjcp.2014.15.16.6531
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Breast Cancer and Breast Self-Examination Practice among Iranian Women in Hamedan, Iran

Abstract: Background: In Iran, breast cancer is the most prevalent cancer in women and a major public health problem. Methods: A cross sectional study was carried out to determine knowledge on breast cancer and breast selfexamination (BSE) practices of 384 females living in the city of Hamadan, Iran. A purposive sampling method was adopted and data were collected via face-to-face interviews based on a validated questionnaire developed for this study. Results: Among respondents 268 (69.8%) were married and 144 (37.5%) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
35
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 23 publications
12
35
4
Order By: Relevance
“…Moreover, this study may inform Jordanian health care providers to improve cancer knowledge, prevention and early detection among older adult individuals. The findings of this study was consistent with others who reported that the participants believed that active cigarette smoking was related to cancer (Akhtari-Zavare, Ghanbari-Baghestan, Latiff, Matinnia, et al, 2014). This indicates that the participants had worthy awareness about one of the highest risk factors to cancer.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, this study may inform Jordanian health care providers to improve cancer knowledge, prevention and early detection among older adult individuals. The findings of this study was consistent with others who reported that the participants believed that active cigarette smoking was related to cancer (Akhtari-Zavare, Ghanbari-Baghestan, Latiff, Matinnia, et al, 2014). This indicates that the participants had worthy awareness about one of the highest risk factors to cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Many factors have been perceived by older adults as playing a critical role in cancer development that may include unhealthy food (Choe et al, 2006); smoking and excessive work and stress (Tawalbeh and Ahmad, 2013;Dardas and Ahmad, 2013). Additional factors may include age (Linsell et al, 2008); not attending regular screening (Akhtari-Zavare et al, 2014), not performing regular exercise (Robb, Miles, and Wardle, 2004) and having a family history (Valentinya et al, 2012;Raj et al, 2012). Health information is important for older adults to raise their awareness of factors that could be related to cancer (Kyle et al, 2012).…”
Section: Perceived Factors Related To Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, Johnson and Dickson-Swift stated that young women believed that they were not at the risk of developing breast cancer (31). In another research performed on female students in Malaysia, Aktari denoted that inattention of young women to the risk of breast cancer might be due to the false perception that they are generally healthy and do not need to perform BSE (23). Collective evaluation of the perceptions of women toward BSE could contribute to designing appropriate educational interventions to affect the attitudes toward breast cancer screening (8,32).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the studies conducted in other countries (21,22). For instance, only 19.6% of the students in Malaysia have been reported to perform BSE (23).…”
Section: Discussionmentioning
confidence: 99%